Psychiatric genetics - Arribas-Ayllon, Michael, author.
1 online resource.
Keywords: Psychiatric genetics has become 'Big Biology'. This may come as a surprising development to those familiar with its controversial history. From eugenic origins and contentious twin studies to a global network of laboratories employing high-throughput genetic and genomic technologies, biological research on psychiatric disorders has become an international, multidisciplinary assemblage of massive data resources. How did psychiatric genetics achieve this scale? How is it socially and epistemically organized? And how do scientists experience this politics of scale? Psychiatric Genetics: From Hereditary Madness to Big Biology develops a sociological approach of exploring the origins of psychiatric genetics by tracing several distinct styles of scientific reasoning that coalesced at the beginning of the twentieth century. These styles of reasoning reveal, among other things, a range of practices that maintain an extraordinary stability in the face of radical criticism, internal tensions and scientific disappointments. The book draws on a variety of methods and materials to explore these claims. Combining genealogical analysis of historical literature, rhetorical analysis of scientific review articles, interviews with scientists, ethnographic observations of laboratory practices and international conferences, this book offers a comprehensive and detailed exploration of both local and global changes in the field of psychiatric genetics.